2008
DOI: 10.1080/00140130701747509
|View full text |Cite
|
Sign up to set email alerts
|

Bone conduction reception: Head sensitivity mapping

Abstract: This study sought to identify skull locations that are highly sensitive to bone conduction (BC) auditory signal reception and could be used in the design of military radio communication headsets. In Experiment 1, pure tone signals were transmitted via BC to 11 skull locations of 14 volunteers seated in a quiet environment. In Experiment 2, the same signals were transmitted via BC to nine skull locations of 12 volunteers seated in an environment with 60 decibels of white background noise. Hearing threshold leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
36
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 19 publications
5
36
0
Order By: Relevance
“…Many behavioural studies have provided evidence that the mastoid is generally more sensitive to bone conduction stimulation than the forehead (Watson 1938;Studebaker 1967;Weston et al 1967;Small et al 2007;McBride et al 2008). Weston et al found that average thresholds for adults at the forehead for 500 Hz were 15 to 20 dB higher (i.e., worse) than thresholds at the mastoid.…”
Section: Skull Locationmentioning
confidence: 96%
“…Many behavioural studies have provided evidence that the mastoid is generally more sensitive to bone conduction stimulation than the forehead (Watson 1938;Studebaker 1967;Weston et al 1967;Small et al 2007;McBride et al 2008). Weston et al found that average thresholds for adults at the forehead for 500 Hz were 15 to 20 dB higher (i.e., worse) than thresholds at the mastoid.…”
Section: Skull Locationmentioning
confidence: 96%
“…However, bone conduction hearing is a much more complex and less understood process than that of air conduction. [18] Thus we need to understand bone conduction auditory feedback including the occlusion effect of protection devices. In addition, future studies should also focus on more basic research conducted on bone conduction interfaces to identify effective locations of bone conduction vibrators and to ensure that their use does not impede the safety and survivability of military personnel.…”
Section: Conclusion and Suggestionmentioning
confidence: 99%
“…[19] Moreover, voice type such as male or female and background noise levels should be considered in future studies. [18] Since chronic NIHL is most commonly caused by prolonged exposure to high levels of noise, to prevent manufacturing and construction workers from developing NIHL, [17] effective hearing protection devices and communicating though bone conduction must be used.…”
Section: Conclusion and Suggestionmentioning
confidence: 99%
“…However, the standards are aimed toward clinical use rather than communication applications (Henry and Letowski, 2007;McBride et al, 2008b). The focus of the standards is on only one bone transducer model (RadioEar B-71) and on only two skull locations (forehead and mastoid process).…”
Section: Introductionmentioning
confidence: 99%
“…Bone conduction transducers can also be used without obstructing a listener's ears and without interfering with hearing protection devices. These benefits make bone conduction an attractive means for radio communication, and several laboratories have conducted investigations using a variety of bone conduction transducer devices placed at various skull locations (e.g., McBride et al, 2008a;McBride et al, 2008b;Osafo-Yeboah et al, 2009;Stanley and Walker, 2009;Tran and Letowski, 2010;McBride et al, 2011).…”
Section: Introductionmentioning
confidence: 99%